A multi-mineral immobilization system based on solid waste and preparation method thereof

Through the preparation of a multi-mineral immobilization system for all solid waste raw materials, the problem of cement clinker production relies on non-renewable resources, and the characteristics of early strength, fast condensation, and fast hardness are achieved, and the production of low-carbon and environmentally friendly cement clinker is met, satisfying the market Demand and carbon emission reduction targets.

CN118529956BActive Publication Date: 2024-12-13INNER MONGOLIA ACADEMY OF SCIENCE & TECHNOLOGY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410993308.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-24
Publication Date
2024-12-13
Estimated Expiration
2044-07-24

AI Technical Summary

Technical Problem

The existing cement clinker relies on non-renewable resources in the production process, resulting in high production costs, large carbon emissions, and difficult to meet market demand.

Method used

The multi-mineral immobilization system is prepared by using all solid waste raw materials. By mixing coal gangue, calcium carbide slag and desulfurization gypsum, and adding modified montmorillonite, the multi-stage calcination conditions are controlled to generate early-strength, fast-condensing, and fast-hardening silicate. Immobilization system mainly composed of calcium, calcium sulfosilicate and calcium sulfaaluminate.

Benefits of technology

It has achieved complete replacement of non-renewable resources, reduced energy consumption and carbon emissions, improved the early strength and later stability of cement clinker, and has economic benefits and market potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118529956B_ABST
    Figure CN118529956B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of solid waste resource utilization, and specifically to a multi-mineral immobilization system based on solid waste and a preparation method thereof. The present invention uses all-solid waste raw materials to completely replace non-renewable resources to prepare cement clinker, and achieves structural deconstruction of coal gangue and carbide slag by adding modified montmorillonite and controlling calcination conditions, and successfully generates a multi-mineral immobilization system mainly composed of dicalcium silicate, calcium sulfosilicate and calcium sulfoaluminate; the multi-mineral immobilization system has the characteristics of early strength, rapid setting and rapid hardening, and meets the requirements of green and low-carbon development of today's building materials industry, has certain economic benefits, and has huge market potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid waste resource utilization, and in particular to a multi-mineral immobilization system based on solid waste and a preparation method thereof. Background Art

[0002] As the main source of carbon emissions, the cement industry is crucial to achieving the goals of carbon peak and carbon neutrality in my country and even the world by promoting its carbon emission reduction. As one of the technical approaches to reduce CO2 emissions in clinker production and cement preparation, the development of low-carbon cement has great potential to further reduce CO2 emissions in the cement industry and is a key technical field for the cement industry to achieve carbon emission reduction. Dicalcium silicate-calcium sulphoaluminate-calcium sulphosilicate cement not only combines the advantages of silicate cement and sulphoaluminate cement, but also has low energy consumption and carbon emissions. It is a new low-carbon cement system with broad application prospects.

[0003] Calcium sulfosilicate, calcium sulfoaluminate and dicalcium silicate minerals have the advantages of low limestone demand, low calcination temperature and low carbon dioxide emissions, and are low-carbon mineral components. Usually, the above three mineral components are made of limestone, bauxite and gypsum as raw materials, and are calcined at low temperatures. They have the characteristics of fast setting speed, high early performance and stable performance in the middle and late stages. At present, the raw materials for producing cement clinker with calcium sulfosilicate, calcium sulfoaluminate and dicalcium silicate as the main mineral components are still mainly non-renewable resources. Among them, the high quality requirements and production costs of the raw material bauxite have restricted the development of this type of material, resulting in a low annual output of cement clinker containing calcium sulfosilicate, calcium sulfoaluminate and dicalcium silicate, which is difficult to meet the growing market demand.

[0004] In order to save production costs, reduce resource consumption and reduce environmental pollution, the use of industrial solid waste as raw materials to prepare this type of cement clinker not only promotes the resource utilization of industrial solid waste, but is also an effective way to help the cement industry achieve the "dual carbon" goal. However, at present, the preparation of cement clinker can only use solid waste to replace part of limestone, bauxite or natural gypsum, and the production process still relies heavily on non-renewable resources.

[0005] Therefore, providing a new multi-mineral immobilization system based on solid waste to solve the above problems has obvious research-oriented value. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a multi-mineral immobilization system based on solid waste and a preparation method thereof. The present invention uses all-solid waste raw materials to completely replace non-renewable resources to prepare cement clinker, and achieves structural deconstruction of coal gangue and carbide slag by adding modified montmorillonite and controlling calcination conditions, and successfully generates a multi-mineral immobilization system mainly composed of dicalcium silicate, calcium sulfosilicate and calcium sulfoaluminate; the multi-mineral immobilization system has the characteristics of early strength, rapid setting and rapid hardening, and meets the requirements of green and low-carbon development of today's building materials industry, has certain economic benefits, and has huge market potential.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] A method for preparing a multi-mineral immobilization system based on solid waste comprises the following steps:

[0009] S1. Mix 40-45 parts of coal gangue, 35-40 parts of carbide slag and 17-22 parts of desulfurized gypsum by mass and stir for 1-2h to obtain a mixed initial material;

[0010] S2. Mix 60-80 parts of the initial mixed material, 20-30 parts of modified montmorillonite, and 20-30 parts of water in parts by mass to obtain a final mixed material;

[0011] S3. The mixed final material is pressed, dried, and calcined in stages under a protective atmosphere, and then cooled to obtain the multi-mineral immobilization system;

[0012] The modified montmorillonite is prepared by the following preparation method:

[0013] 15-20 parts of montmorillonite by mass are crushed, immersed in 60-80 parts of saturated aluminum chloride solution and fully stirred, immersed for 24-28 hours, and then the pH of the solution is adjusted to 9-12, immersed for 2-3 hours, and taken out after drying to obtain the modified montmorillonite.

[0014] Preferably, in S3, the staged calcination specifically comprises the following steps:

[0015] S11. The first stage of calcination: the mixed final material is heated to 150-300 ° C;

[0016] S12. The second stage of calcination: Based on the first stage of calcination, the temperature is raised to 300-700°C;

[0017] S13. The third stage of calcination: on the basis of the second stage of calcination, the temperature is raised to 700-900°C;

[0018] S14. The fourth stage of calcination: on the basis of the third stage of calcination, the temperature is raised to 900-1050°C;

[0019] S15. Fifth stage calcination: Based on the fourth stage calcination, the temperature is raised to 1050~1250℃

[0020] Preferably, the heating rate of the first stage calcination is 9-11°C / min; the heating rate of the second stage calcination is 5-7°C / min; the heating rate of the third stage calcination is 1-3°C / min; the heating rate of the fourth stage calcination is 1-3°C / min, and the heating rate of the fifth stage calcination is 1-3°C / min.

[0021] Preferably, the calcination time of the first stage calcination, the second stage calcination, the third stage calcination, the fourth stage calcination and the fifth stage calcination is 30-40 minutes.

[0022] Preferably, in S1, the coal gangue is powdered coal gangue with a particle size of ≤0.07 mm; the carbide slag is powdered carbide slag with a particle size of ≤0.07 mm; and the particle size of the desulfurized gypsum is ≤80 μm.

[0023] Preferably, in S3, the pressing pressure is 18-22 MPa; the drying temperature is 100-120° C., and the drying time is 24-28 h.

[0024] Preferably, in S3, the specific cooling method is air cooling.

[0025] Preferably, in S3, the protective atmosphere is a mixed atmosphere of SO2 and CO2; the flow rate of SO2 is 20-30sccm; and the flow rate of CO2 is 10-15sccm.

[0026] A multi-mineral immobilization system based on solid waste is prepared according to the preparation method.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. The present invention uses industrial solid waste to completely replace non-renewable resources to prepare cement clinker. When coal gangue is used instead of bauxite, it can not only provide aluminum and silicon elements necessary for preparing cement clinker, but the 15-20% carbon content in the coal gangue can also provide a certain heat source in the calcination process, thereby reducing energy consumption;

[0029] 2. In the present invention, modified montmorillonite is added during the preparation process of the multi-mineral immobilization system. The montmorillonite is firstly treated with Al 3+Cationic intercalation replaces the original cations, increases the interlayer distance and porosity of montmorillonite, improves its adsorption capacity, and thus improves the cementing capacity of the multi-mineral immobilization system. Secondly, the generated NaAlO2 contributes to the hydration of the early calcium sulfosilicate-dicalcium silicate composite mineral, thereby improving the early strength of the concrete. In addition, after calcination, the interlayer structure of the modified montmorillonite is partially decomposed, releasing active MgO, which continuously absorbs water and is converted into Mg(OH)2 and exists in the immobilization system. In the later curing process, it can be further converted into magnesite. On the basis of improving the stability of the multi-mineral immobilization system by filling, the damage caused by the expansion and water absorption of calcium sulfoaluminate in the later curing stage can be avoided, and the mechanical properties of the multi-mineral immobilization system can be significantly improved.

[0030] 3. The present invention adopts a multi-stage heating and heat preservation calcination system, and under the action of a protective atmosphere, the generation rate of calcium sulfosilicate, a transition mineral phase, is increased. The generated calcium sulfosilicate and dicalcium silicate generate CSH gel in the middle and late stages of the hydration reaction, which promotes the stable growth of cement strength in the middle and late stages and avoids the problem of strength shrinkage in the late stages. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The present invention is a flow chart of the preparation process of the multi-mineral immobilization system based on solid waste;

[0032] Figure 2 is the XRD spectrum of the multi-mineral immobilization system based on solid waste in Example 1;

[0033] Figure 3 is the XRD spectrum of the multi-mineral immobilization system based on solid waste in Example 2;

[0034] Figure 4 The XRD spectra of the hydration products of the multi-mineral immobilization system based on solid waste in Example 1 at different ages;

[0035] Figure 5 These are the XRD spectra of the hydration products of the solid waste-based multi-mineral immobilization system of Example 2 at different ages. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] See also Figure 1-5 , the present invention provides the following technical solutions:

[0038] In the embodiment, the chemical compositions of the coal gangue raw material, the carbide slag raw material, and the desulfurized gypsum raw material are shown in Table 1:

[0039] Table 1. Chemical composition of coal gangue, carbide slag and desulfurized gypsum

[0040]

[0041] Example 1

[0042] A method for preparing a multi-mineral immobilization system based on solid waste:

[0043] The blocky coal gangue with a particle size of 30-45 mm is placed in a jaw crusher to be crushed into granular coal gangue with a particle size of 3-6 mm; the granular coal gangue is placed in a grinder and ground at a rate of 50 r / min and sieved using a sieving machine to obtain powdered coal gangue with a particle size of less than 0.07 mm. The water-containing calcium carbide slag is placed in an oven at 105°C for drying; the dried calcium carbide slag is placed in a grinder for grinding and sieved using a sieving machine to obtain powdered calcium carbide slag with a particle size of less than 0.07 mm. The desulfurized gypsum with a particle size of less than 80 μm and more than 85% of the particle size of 30-60 μm is placed in a sieving machine for sieving to remove impurities to obtain powdered desulfurized gypsum.

[0044] 15g of montmorillonite was placed in a grinder for grinding until no obvious particles were found. The treated montmorillonite was immersed in 60ml of saturated aluminum chloride solution and stirred thoroughly. After immersion for 24h, the pH value of the solution was adjusted to 10 with sodium hydroxide, and the solution was immersed for another 2h. The solution was dried and taken out to obtain modified montmorillonite.

[0045] Powdered coal gangue, powdered carbide slag and powdered desulfurization gypsum with a mass ratio of 42.57:37.82:19.61 were placed in a mixer and mixed at a speed of 30r / min for 60min. 25g of the uniformly mixed initial material was mixed with 10g of modified montmorillonite and 10g of water. A powder molding machine was used to press it into round cakes with a diameter of 60mm and a height of 5mm at a pressure of 20MPa. The round cakes were then dried in a forced air drying oven at a temperature of 105℃ for 24h.

[0046] The dried round cakes were placed in a high-temperature box furnace for multi-stage heating and insulation calcination. The specific calcination process was as follows: in a mixed atmosphere of SO2 and CO2 (the flow rate of SO2 was 20 sccm; the flow rate of CO2 was 10 sccm), the temperature was increased from 25°C to 300°C at a rate of 10°C / min, and kept at 300°C for 30 minutes; then the temperature was increased from 300°C to 700°C at a rate of 5°C / min, and kept at 700°C for 30 minutes; then the temperature was increased from 700°C to 900°C at a rate of 2°C / min, and kept at 900°C for 30 minutes; then the temperature was increased from 900°C to 1050°C at a rate of 2°C / min, and kept at 1050°C for 30 minutes; finally, the temperature was increased from 1050°C to 1200°C at a rate of 2°C / min, and kept at 1200°C for 30 minutes. After calcination, the mixed material is immediately taken out from the high temperature box furnace and cooled to room temperature by air cooling (the air volume is 0.15Nm during the process of cooling from 1200℃ to 800℃). 3 / kg, the air volume during the cooling process from 800℃ to room temperature is 0.25Nm 3 / kg), and a multi-mineral immobilization system based on solid waste was obtained.

[0047] Example 2: Example 2 is different from Example 1 in the following manner. The only difference is that in Example 2, the calcination process in Example 1 of "raising the temperature from 1050°C to 1200°C at a rate of 2°C / min, and keeping warm at 1200°C for 30 min" is changed to "raising the temperature from 1050°C to 1250°C at a rate of 2°C / min, and keeping warm at 1250°C for 30 min". The remaining steps in Example 2 and Example 1 are exactly the same.

[0048] Example 3

[0049] A method for preparing a multi-mineral immobilization system based on solid waste:

[0050] The blocky coal gangue with a particle size of 30-45 mm is placed in a jaw crusher to be crushed into granular coal gangue with a particle size of 2-8 mm; the granular coal gangue is placed in a grinder and ground at a rate of 50 r / min and sieved using a sieving machine to obtain powdered coal gangue with a particle size of less than 0.07 mm. The water-containing calcium carbide slag is placed in an oven at 102°C for drying; the dried calcium carbide slag is placed in a grinder for grinding and sieved using a sieving machine to obtain powdered calcium carbide slag with a particle size of less than 0.07 mm. The desulfurized gypsum with a particle size of less than 80 μm and more than 85% of the particle size of 30-60 μm is placed in a sieving machine for sieving to remove impurities to obtain powdered desulfurized gypsum.

[0051] 20g of montmorillonite was placed in a grinder for grinding until no obvious particles were found. The treated montmorillonite was immersed in 70ml of saturated aluminum chloride solution and stirred thoroughly. After immersion for 24h, the pH value of the solution was adjusted to 11 with sodium hydroxide, and the solution was immersed for another 2h. The solution was dried and taken out to obtain modified montmorillonite.

[0052] Powdered coal gangue, powdered carbide slag and powdered desulfurization gypsum in a mass ratio of 41:38:21 were placed in a mixer and mixed at a speed of 28r / min for 120min. 25g of the evenly mixed initial material was mixed with 15g of modified montmorillonite and 10g of water. A powder molding machine was used to press it into round cakes with a diameter of 58mm and a height of 4.5mm at a pressure of 18MPa. The round cakes were then dried in a forced air drying oven at a temperature of 103℃ for 26h.

[0053] The dried round cakes were placed in a high-temperature box furnace for multi-stage heating and insulation calcination. The specific calcination process was as follows: in a mixed atmosphere of SO2 and CO2 (the flow rate of SO2 was 30 sccm; the flow rate of CO2 was 15 sccm), the temperature was increased from 24°C to 280°C at a rate of 9°C / min, and kept at 280°C for 30 minutes, and then the temperature was increased from 280°C to 680°C at a rate of 4.5°C / min, and kept at 680°C for 35 minutes; then the temperature was increased from 680°C to 880°C at a rate of 1.5°C / min, and kept at 880°C for 33 minutes; then the temperature was increased from 880°C to 1030°C at a rate of 1.5°C / min, and kept at 1030°C for 30 minutes; finally, the temperature was increased from 1030°C to 1230°C at a rate of 2°C / min, and kept at 1230°C for 35 minutes. After calcination, the final mixed material is immediately taken out from the high temperature box furnace and cooled to room temperature by air cooling (the air volume is 0.15Nm during the process of cooling from 1230℃ to 800℃). 3 / kg, the air volume during the cooling process from 800℃ to room temperature is 0.25Nm 3 / kg), and a multi-mineral immobilization system based on solid waste was obtained.

[0054] Example 4

[0055] A method for preparing a multi-mineral immobilization system based on solid waste:

[0056] The blocky coal gangue with a particle size of 30-40 mm is placed in a jaw crusher to be crushed into granular coal gangue with a particle size of 1-10 mm; the granular coal gangue is placed in a grinder and ground at a rate of 50 r / min and sieved using a sieving machine to obtain powdered coal gangue with a particle size of less than 0.07 mm. The water-containing calcium carbide slag is placed in an oven at 104°C for drying; the dried calcium carbide slag is placed in a grinder for grinding and sieved using a sieving machine to obtain powdered calcium carbide slag with a particle size of less than 0.07 mm. The desulfurized gypsum with a particle size of less than 80 μm and more than 85% of the particle size of 30-60 μm is placed in a sieving machine for sieving to remove impurities to obtain powdered desulfurized gypsum.

[0057] 18g of montmorillonite was placed in a grinder for grinding until no obvious particles were found. The treated montmorillonite was immersed in 65ml of saturated aluminum chloride solution and stirred thoroughly. After immersion for 26h, the pH value of the solution was adjusted to 9 with sodium hydroxide, and the solution was immersed for another 3h. The solution was dried and taken out to obtain modified montmorillonite.

[0058] Powdered coal gangue, powdered carbide slag and powdered desulfurization gypsum in a mass ratio of 44:36:20 were placed in a mixer and mixed at a speed of 29r / min for 80min. 25g of the evenly mixed initial material was mixed with 15g of modified montmorillonite and 11g of water. A powder molding machine was used to press it into round cakes with a diameter of 61mm and a height of 5.5mm at a pressure of 22MPa. The round cakes were then dried in a forced air drying oven at a temperature of 105℃ for 25h.

[0059] The dried round cakes were placed in a high-temperature box furnace for multi-stage heating and insulation calcination. The specific calcination process was as follows: in a mixed atmosphere of SO2 and CO2 (the flow rate of SO2 was 28 sccm; the flow rate of CO2 was 14 sccm), the temperature was increased from 24°C to 290°C at a rate of 11°C / min, and kept at 290°C for 30 minutes, and then the temperature was increased from 290°C to 690°C at a rate of 5.5°C / min, and kept at 690°C for 35 minutes; then the temperature was increased from 690°C to 890°C at a rate of 2.5°C / min, and kept at 890°C for 33 minutes; then the temperature was increased from 890°C to 1040°C at a rate of 2.5°C / min, and kept at 1040°C for 30 minutes; finally, the temperature was increased from 1040°C to 1220°C at a rate of 2.5°C / min, and kept at 1220°C for 35 minutes. After calcination, the final mixed material is immediately taken out from the high temperature box furnace and cooled to room temperature by air cooling (the air volume during the process of cooling from 1220℃ to 800℃ is 0.15Nm 3 / kg, the air volume during the cooling process from 800℃ to room temperature is 0.25Nm 3 / kg), and a multi-mineral immobilization system based on solid waste was obtained.

[0060] In Example 1-4, a heating and heat preservation calcination system is used in five stages to ensure that the initial mineral components are completely decomposed and the target mineral components are fully reconstructed. The main principles of the heating and heat preservation calcination system are as follows:

[0061] The first and second stage calcination are the initial mineral component decomposition stages, wherein the desulfurized gypsum undergoes a dehydration reaction in the first stage calcination interval and is converted into calcium sulfate, and the decomposition reaction chemical formula is shown in formula (1). In the second stage calcination interval, the main mineral component of the coal gangue, kaolinite, undergoes a dehydroxylation reaction and is converted into a metakaolinite structure, and the decomposition reaction chemical formula is shown in formula (2); the boehmite in the coal gangue undergoes a decomposition reaction and is converted into activated alumina; in addition, during the second stage calcination process, the calcium hydroxide in the carbide slag undergoes a decomposition reaction and is converted into calcium oxide, and the decomposition reaction chemical formula is shown in formula (3). The third and fourth stage calcination are the transition phase mineral component formation stages, wherein in the third stage calcination interval, the metakaolinite and calcium oxide undergo a solid phase reaction to form a transition mineral component, calcium aluminum feldspar, as shown in formula (4); the activated alumina and calcium oxide undergo a solid phase reaction to form a transition mineral component, calcium heptaaluminate, as shown in formula (5). The fourth and fifth calcination stages are the target mineral component reconstruction stages, wherein amorphous silicon oxide undergoes a solid phase reconstruction reaction with calcium oxide in the fourth calcination interval to form dicalcium silicate, as shown in formula (6); amorphous aluminum oxide undergoes a solid phase reconstruction reaction with calcium oxide and calcium sulfate to form tetracalcium sulfoaluminate, as shown in formula (7). The fifth calcination interval is the main formation stage of the target mineral component, wherein the transitional mineral calcite reacts with calcium oxide to be converted into dicalcium silicate and tricalcium aluminate, as shown in formula (8); tricalcium aluminate further reacts with calcium sulfate and aluminum oxide, as shown in formula (9); the transitional mineral calcite reacts with calcium oxide and calcium sulfate to be converted into tetracalcium sulfoaluminate and dicalcium silicate, as shown in formula (10); the transitional mineral dodecaluminate reacts with aluminum oxide and calcium sulfate to be converted into tetracalcium sulfoaluminate, as shown in formula (11); and dicalcium silicate undergoes a solid phase reaction with calcium sulfate to form calcium sulfosilicate, as shown in formula (12).

[0062] (Formula 1)

[0063] (Formula 2)

[0064] (Formula 3)

[0065] (Formula 4)

[0066] (Formula 5)

[0067] (Formula 6)

[0068] (Formula 7)

[0069] (Formula 8)

[0070] (Formula 9)

[0071] (Formula 10)

[0072] (Formula 11)

[0073] (Formula 12)

[0074] The multi-mineral immobilization system prepared in Example 1-2 was subjected to XRD test, and the test results were as follows: Figure 2 , Figure 3 As shown. Figure 2 , Figure 3 It can be seen that the main mineral components of the multi-mineral immobilization system of Example 1 are dicalcium silicate, calcium sulfosilicate, and calcium sulfoaluminate; the main mineral components of the multi-mineral immobilization system of Example 2 are dicalcium silicate, calcium sulfosilicate, calcium sulfoaluminate and calcium sulfate.

[0075] according to Figure 2 , Figure 3 Based on the Rietveld quantitative analysis principle, the mineral components of the multi-mineral immobilization system of Examples 1 to 2 were quantitatively analyzed using EXPGUI-GSAS II software. The results are shown in Table 2:

[0076] Table 2. Quantitative analysis results of mineral components of the multi-mineral immobilization system of Example 1-2

[0077]

[0078] The multi-mineral immobilization system and water obtained in Examples 1-2 were weighed according to a water-cement ratio of 0.30; water was first poured into a cement paste mixer, and then the multi-mineral immobilization system was added to the water; the multi-mineral immobilization system and water were stirred according to the operating procedures of the cement paste mixer; after stirring evenly, it was poured into a mold with a size of 20mm×20mm×20mm, and placed on a cement mortar vibration table for vibration; finally, the film was placed in a standard curing room (temperature 20±2℃, relative humidity 97%) for curing. After curing to the specified age, the compressive strength of the cementitious system was tested according to the general cement paste strength test standard GB / T 17671-2021 Cement mortar strength test method (ISO method), and the results are shown in Table 3. As can be seen from Table 3, the compressive strengths of the multi-mineral immobilization systems of Example 1 and Example 2 are 7.31MPa and 15.46MPa, respectively, at a hardening age of 3h. The hardening age of 3h~3d is the rapid growth period of the compressive strength of the multi-mineral immobilization system, and the hardening age of 3d~28d is the slow growth period of the compressive strength of the multi-mineral immobilization system.

[0079] Table 3. Compressive strength of the multi-mineral immobilization system of Examples 1-2

[0080]

[0081] The multi-mineral immobilization system of Examples 1-2 was subjected to hydration tests, and XRD spectra of hydration products at hydration ages of 1 d, 7 d, and 28 d were obtained, as shown in FIG4 and FIG5 , respectively.

[0082] The specific steps of the hydration test are as follows: the multi-mineral immobilization system and water obtained in Examples 1-2 are weighed respectively according to a water-binder ratio of 0.30; water is first poured into a cement slurry mixer, and then the multi-mineral immobilization system is added to the water; the multi-mineral immobilization system and water are stirred according to the operating procedures of the cement slurry mixer; after stirring evenly, it is cast into a mold with a size of 20 mm×20 mm×20 mm, and it is placed on a cement mortar vibration table for vibration; finally, it is covered with a film and placed in a standard curing room (temperature 20±2°C, relative humidity 97%) for curing. After curing to the specified hydration age, the central part of the sample is taken and crushed into particles with a diameter of less than 1 mm. To terminate the hydration, the granular sample is soaked in anhydrous ethanol (purity of 99.3%) for 24 hours. The sample after hydration is placed in a drying oven for drying, the drying temperature is 45°C, and the drying time is 24 hours. Then, the dried granular sample is ground and sieved using an agate mortar. Finally, the powder samples with a particle size of less than 74 μm after sieving were placed in a sealed bag for testing the XRD spectrum. As can be seen from the figure, the main hydration product of the multi-mineral immobilization system of Example 1 and Example 2 is ettringite, and the hydration speed is very fast. A large amount of ettringite is generated after hydration for 3 hours; further, Figure 4 , 5 As shown, with the increase of hydration age, Mg(OH)2 is gradually transformed into magnesite, which improves the stability of the multi-mineral immobilization system by filling, and avoids the damage caused by the expansion and water absorption of calcium sulfoaluminate in the later curing stage. The compressive strength data of the multi-mineral immobilization system of Examples 1-2 in Table 3 (the highest compressive strength reached 41.57 MPa) also confirms this view; at the same time, calcium sulfoaluminate almost completely undergoes hydration reaction, and the degree of hydration reaction of dicalcium silicate increases with the increase of hydration age. The hydration degree of calcium sulfosilicate also increases slightly. It is speculated that the reason is that the NaAlO2 loaded in the modified montmorillonite promotes the hydration of calcium sulfosilicate-dicalcium silicate composite mineral.

[0083] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a multi-mineral immobilization system based on solid waste, characterized in that: The following steps are involved: S1. Mix 40-45 parts of coal gangue, 35-40 parts of carbide slag and 17-22 parts of desulfurized gypsum by mass and stir for 1-2h to obtain a mixed initial material, wherein the coal gangue is powdered coal gangue with a particle size of ≤0.07mm; the carbide slag is powdered carbide slag with a particle size of ≤0.07mm; the particle size of the desulfurized gypsum is ≤80μm; S2. Mix 60-80 parts of the initial mixed material, 20-30 parts of modified montmorillonite, and 20-30 parts of water in parts by mass to obtain a final mixed material; S3. The mixed final material is pressed, dried, and calcined in stages under a protective atmosphere, and after cooling, the multi-mineral immobilization system is obtained. The staged calcination specifically comprises the following steps: S11. The first stage of calcination: the mixed final material is heated to 150-300 ° C; S12. The second stage of calcination: Based on the first stage of calcination, the temperature is raised to 300-700°C; S13. The third stage of calcination: on the basis of the second stage of calcination, the temperature is raised to 700-900°C; S14. The fourth stage of calcination: on the basis of the third stage of calcination, the temperature is raised to 900-1050°C; S15. The fifth stage of calcination: on the basis of the fourth stage of calcination, the temperature is raised to 1050~1250℃; The modified montmorillonite is prepared by the following preparation method: 15-20 parts of montmorillonite by mass are crushed, immersed in 60-80 parts of saturated aluminum chloride solution and fully stirred, immersed for 24-28 hours, and then the pH of the solution is adjusted to 9-12, immersed for 2-3 hours, and taken out after drying to obtain the modified montmorillonite.

2. The method for preparing a multi-mineral immobilization system based on solid waste according to claim 1, characterized in that: The heating rate of the first stage calcination is 9-11°C / min; the heating rate of the second stage calcination is 5-7°C / min; the heating rate of the third stage calcination is 1-3°C / min; the heating rate of the fourth stage calcination is 1-3°C / min, and the heating rate of the fifth stage calcination is 1-3°C / min.

3. The method for preparing a multi-mineral immobilization system based on solid waste according to claim 2, characterized in that: The calcination time of the first stage calcination, the second stage calcination, the third stage calcination, the fourth stage calcination and the fifth stage calcination is 30-40 minutes.

4. The method for preparing a multi-mineral immobilization system based on solid waste according to claim 1, characterized in that: In S3, the pressing pressure is 18-22 MPa; the drying temperature is 100-120° C., and the drying time is 24-28 h.

5. The method for preparing a multi-mineral immobilization system based on solid waste according to claim 1, characterized in that: In S3, the specific cooling method is air cooling.

6. The method for preparing a multi-mineral immobilization system based on solid waste according to claim 1, characterized in that: In S3, the protective atmosphere is a mixed atmosphere of SO2 and CO2; the flow rate of SO2 is 20-30sccm; and the flow rate of CO2 is 10-15sccm.

7. A multi-mineral immobilization system based on solid waste, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 6.